Apoptotic and DNA-damaging effects of yttria-stabilized zirconia nanoparticles on human skin epithelial cells - Alzahrani FM (Dove Medical Press, 2019)
Fatimah Mohammed Alzahrani,1 Khadijah Mohammed Saleh Katubi,1 Daoud Ali,2 Saud Alarifi21Chemistry Department, College of Science, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Zoology, College of Science, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Saud AlarifiDepartment of Zoology, College of Science, King Saud University, PO Box 2455, Riyadh 11451, Saudi ArabiaTel +966 1 467 9816Fax +966 4 678 514Email salarifi@ksu.edu.saBackground: Yttria-stabilized zirconia (Y2O3/ZrO2) nanoparticles are one of the important nanoparticles extensively used in manufacturing of plastics, textiles, catalyst, etc. Still, the cytotoxic and apoptotic effects of yttria-stabilized zirconia nanoparticles have not been well identified on human skin keratinocyte (HaCaT) cells. Therefore, in this study, we have designed to examine the cytotoxic potential of yttria-stabilized zirconia nanoparticles in HaCaT cells.Methods: Prior to treatment, the yttria-stabilized zirconia nanoparticles were characterized by using different advanced instruments viz. dynamic light scattering (DLS), scanning electron microscope (SEM) and transmission electron microscope (TEM). Cell viability of HaCaT cells was measured by using MTS and NRU assays and viability of cells was reduced in a dose- and time-dependent manner.Results: Reduction in the viability of cells was correlated with the rise of reactive oxygen species generation, increased caspase-3, mitochondria membrane potential and evidence of DNA strand breakage. These were consistent with the possibility that mitochondria damage can play a significant role in the cytotoxic response. Moreover, the activity of oxidative enzymes such as lipid peroxide (LPO) was increased and glutathione was reduced in HaCaT cells exposed with yttria-stabilized zirconia nanoparticles. It is also important to indicate that HaCaT cells appear to be more susceptible to yttria-stabilized zirconia nanoparticles exposure after 24 hrs.Conclusion: This result provides a dose- and time-dependent apoptosis and genotoxicity of yttria-stabilized zirconia nanoparticles in HaCaT cells.Keywords: yttria-stabilized zirconia nanoparticles, oxidative stress, HaCaT cells, geno toxicity, apoptosis